ANALYSIS OF THE INFLUENCE OF WORK-LIFE BALANCE AND ORGANIZATIONAL CULTURE ON WORK ENGAGEMENT THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AMONG BINTARA MEMBERS OF PUBLIC RELATIONS DIVISION OF CENTRAL JAVA REGIONAL POLICE - ARISTIYANI, ANA; WIDHIASTUTI, HARDANI; DEWI, RUSMALIA (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2024)
This study aims to assess the influence of work-life balance and organizational culture on work engagement, with job satisfaction serving as a mediating variable, among Bintara personnel in the Public Relations Division of the Central Java Regional Police. A quantitative correlational approach was used, with 39 Bintara respondents participating. The results show that organizational culture has a significant impact on work engagement, while work-life balance does not exhibit a substantial effect. Furthermore, job satisfaction does not mediate the relationship between work-life balance, organizational culture, and work engagement. The validity tests reveal that all variables have AVE values greater than 0.5 and Cronbach's Alpha scores above 0.7, indicating high validity and reliability. These findings highlight the important role of organizational culture in promoting work engagement among police officers and recommend improvements to work-life balance policies within police institutions. ABSTRAKPenelitian ini bertujuan untuk mengkaji pengaruh work-life balance dan budaya organisasi terhadap work engagement, dengan kepuasan kerja sebagai variabel mediasi, pada personel Bintara Divisi Humas Polda Jawa Tengah. Pendekatan korelasional kuantitatif digunakan, dengan partisipasi 39 responden Bintara. Hasil penelitian menunjukkan bahwa budaya organisasi memiliki pengaruh yang signifikan terhadap work engagement, sedangkan work-life balance tidak menunjukkan pengaruh yang substansial. Lebih lanjut, kepuasan kerja tidak memediasi hubungan antara work-life balance, budaya organisasi, dan work engagement. Uji validitas menunjukkan bahwa semua variabel memiliki nilai AVE lebih besar dari 0,5 dan skor Cronbach's Alpha di atas 0,7, yang menunjukkan validitas dan reliabilitas yang tinggi. Temuan ini menyoroti peran penting budaya organisasi dalam meningkatkan work engagement di kalangan polisi dan merekomendasikan perbaikan kebijakan work-life balance di dalam institusi kepolisian.